EFEKTIVITAS YOGA TERHADAP KUALITAS TIDUR IBU HAMIL - Sri Delima Harahap; Sri Utami; Nurul Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
During pregnancy, the mother will experience both physical and psychological changes, one of the psychic changesexperienced by pregnant women in the form of sleep disorders. Fulfilling the needs of sleep in pregnant women is animportant thing to be able to maintain the condition of pregnant women in the optimal state during pregnancy. One waythat can be done to overcome sleep disorders in pregnant women is to do yoga. This study aims to determine theeffectiveness of yoga on sleep quality of pregnant women. This research uses Quasy experiment design with nonequivalentcontrol group design divided into experiment and control group. This research was conducted in KualuVillage Working area of Puskesmas Tambang with total sample 34 respondents taken by purposive sampling technique.The measuring tool used in the two groups is the PSQI (Pittsburgh Sleep Quality Index) questionnaire. The dataanalysis used dependent T test and independent T test. The results of this study indicate effective yoga on maternal sleepquality with p value (0.000) <alpha (0,05). The results of this study can be used as a reference to use yoga as analternative in overcoming complaints of sleep quality disorders in pregnant women.Keyword: Pregnantwomen, sleep quality, yoga.